Classification of Scout Skills Using Naive Bayes Algorithm - Rizky Yudha Pramudhika; Rifki Fahrial Zainal; Rani Purbaningtyas (JEECS (Journal of Electrical Engineering and Computer Sciences), 2017)
In the development of skills and skills of students Scout often finds the problem is the difficulty of developing theskills of learners caused by mistakes in determining the skills dominated by learners. How you can do it to solve thatproblem is by making a class determination or classification of areas of expertise controlled by the learner. Thisstudy aims to build a system to determine the inner class Scout skills area using Naïve Bayes algorithm for ScoutCoach to determine the area of expertise of learners. So Scout Coach can develop the skills of learners inaccordance with the areas of expertise that are owned optimally. Assessment criteria used are the values of GeneralKnowledge, Scout Knowledge, Sign Language (Password, Morse, Semaphore), Node Bond, Pioneering, and HastaKarya. All assessment criteria are used numerically. The resulting classification is the students who are included inthe class Intelligence (Intelligence), Physical (Strength), or Creativity. The results of this study is a program that canperform calculations to determine skill class scout field. The Scouting Skill Classification Program using the NaïveBayes Algorithm has been tested and its accuracy or accuracy is 100%.